Current-mirror phase-shifter oscillator - Pookaiyaudom, s.; Samootrut, K. (My University, 1987)
Recently proposed differential current mirrors have been used to realise phase-shifter circuits. Two of these phase-shifters are then cascaded to form a high-performance sinusoidal oscillator, where all active functional blocks are current mirrors. © 1987, The Institution of Electrical Engineers. All rights reserved.
Keywords: Circuit theory and design; Oscillators